Zinc in Oral Health and Disease: A Narrative Review - Anggun Rafisa; Felisha Febriane Balafif; Nuroh Najmi; Faisal Kuswandani (Sean Institute, 2026)
Zinc is an essential trace element that plays a fundamental role in maintaining oral health through its structural, catalytic, and regulatory functions. It is involved in numerous biological processes, including immune modulation, antioxidant defense, collagen synthesis, mineralization, cellular signaling, and tissue repair, all of which contribute to oral tissue homeostasis. Recent evidence has highlighted the importance of zinc homeostasis, regulated by zinc transporters and metallothioneins, in preserving normal tooth development, periodontal integrity, and wound healing. Zinc also exerts antimicrobial, anti-inflammatory, and remineralizing effects, supporting its role in the prevention and management of dental caries, periodontal diseases, and oral mucosal disorders. Furthermore, advances in biomaterials and nanotechnology have expanded the therapeutic applications of zinc through zinc-containing restorative materials, zinc oxide nanoparticles, and zinc-L-carnosine, which demonstrate promising antimicrobial, regenerative, and tissue-healing properties. Emerging evidence also suggests that salivary zinc and zinc-associated proteins may serve as potential biomarkers for oral squamous cell carcinoma, although their diagnostic and therapeutic significance remains to be fully established. Despite these promising findings, the clinical application of zinc-based interventions is limited by inconsistencies in dosage, bioavailability, and treatment protocols. This narrative review summarizes the current evidence regarding the biological functions of zinc, its role in oral diseases, therapeutic applications in dentistry, and future perspectives, highlighting zinc as a promising adjunct in maintaining oral health and improving clinical outcomes.